Pemanfaatan Tepung Kulit Bawang Merah (Allium ascalonicum) Sebagai Imbuhan Pakan Terhadap Penampilan, Profil Darah Dan Kolesterol Pada Puyuh Petelur (Faculty of Animal Science, Universitas Brawijaya, 2017)
The main bioactive compound in skin Allium ascalonicum is quercetin, which serves as antibacterial and anticholesterol agent. The purpose of this research was to investigate the effect of skin Allium ascalonicum powder supplementation on blood profile and egg cholesterol content of quail. One hundred and forty-four quails were randomly allocated in 24 flocks, consisting 4 treatments and 6 replications. Each replication consisted of 6 quails. The treatments used were P0: basal diet (control), P1: basal diet +1% skin powder Allium ascalonicum, P2: basal diet + 2% skin of Allium ascalonicum powder, and P3: basal diet + 3% skin of Allium ascalonicum powder. Variables observed were blood erythrocytes, hemoglobin and egg cholesterol content. Data were analyzed using one-way Analysis of Variance (ANOVA). Significant data was then further analyzed using Duncan Multiple Range Test. The result showed that there was no significant effect (P>0.05) of shallot skin powder on blood erythrocytes and hemoglobin of quail.There was significant effect (P<0.05) of skin Allium ascalonicum powder supplementation on egg cholesterol content. Supplementation of skin Allium ascalonicum powder at the level of 3% (P3) could decrease egg cholesterol content compared to control (682.20 mg/dL vs 729.80 mg/dL). The conclusion of this research is that skin of Allium ascalonicum powder supplementation could decrease cholesterol content in quail egg.